A fundamental differential system of 3-dimensional Riemannian geometry - Albuquerque, Rui (2019)
We briefly recall a fundamental exterior differential system of Riemannian geometry and apply it to the case of three dimensions. Here we find new global tensors and intrinsic invariants of oriented Riemannian 3-manifolds. In particular, we develop the study of ∇Ric. The exterior differential system leads to a remarkable Weingarten type equation for immersed surfaces in hyperbolic 3-space. A new independent proof for low dimensions of the structural equations gives new insight on the intrinsic exterior differential system.